Suspended Lives: Lucy Caldwell’s Three Sisters in Post-Agreement Belfast - Csikai, Zsuzsa (Hungarian Journal of English and American Studies, 2022)
Lucy Caldwell’s 2016 adaptation of Chekhov’s Three Sisters relocates the play into Belfast in the 1990s. This paper examines Caldwell’s adaptation in the context of Irish and Northern Irish rewritings of Chekhov’s dramatic works, paying attention to the motives behind appropriating the Russian works for Irish audiences. Inspired by the perceived affinity between the two seemingly distant cultures, Irish authors have tended to adapt Chekhov (and other Russian classics) to reflect on their own social, cultural, and political environment, often with the aim of shaping the cultural-political landscape of their present. Similarly to earlier Chekhov adaptations, Caldwell’s play engages not only with the original Russian work, but, most importantly, with the cultural-political context of its setting—the five hopeful years preceding the Belfast Agreement (1998), as well as the post-Agreement context of its writing. The play allows its audience in 2016 a complex, retrospective, re-evaluative view of the achievements of the peace process from the vantage point of the early twenty-first century. (ZSCS)